2014
DOI: 10.14366/usg.14023
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrasonographic features of vascular closure devices: initial and 6-month follow-up results

Abstract: Purpose:This study aimed to evaluate the ultrasonographic findings for various types of vascular closure devices (VCDs) immediately after the angiographic procedure and at 6-month follow-up.Methods:We included 18 VCDs including Angio-Seal (n=4), FemoSeal (n=8), ExoSeal (n=3), Perclose (n=2), and StarClose (n=1) in this study. Four patients were implanted with 2 VCDs at the each side of bilateral femoral arteries, while the remaining 8 patients were inserted 1 VCD at the right femoral artery. Ultrasonography wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The surgeon should pull the handle of the closure device linearly[ 14 ] and then remove it smoothly. Studies have shown that the release of the vascular closure device under ultrasound guidance can reduce the number of complications[ 15 - 17 ]. In addition, although the vascular closure device has significant advantages in closing large-sized blood vessels, its operation is complicated[ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The surgeon should pull the handle of the closure device linearly[ 14 ] and then remove it smoothly. Studies have shown that the release of the vascular closure device under ultrasound guidance can reduce the number of complications[ 15 - 17 ]. In addition, although the vascular closure device has significant advantages in closing large-sized blood vessels, its operation is complicated[ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Boschewitz et al 6 previously showed the efficacy of repeat ExoSeal closure but did not examine the time dependence. After implantation, Exo-Seal has been suggested to absorb completely in 2 to 3 months, but Choo et al 9 found only partial absorption of an ExoSeal implant in follow-up ultrasound at 6 months. Thus, it is possible that the interval between ExoSeal implantation and complete absorption may differ among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Third, it is an anchorless device that releases only a bioabsorbable plug entirely into the extravascular space, so it does not easily influence intra-arterial wall responses such as intimal hyperplasia. 13 Therefore, it is suitable for repeated punctures and site closures. 4 There are some reports that describe off-label use of ExoSeal VCDs for antegrade puncture closure 3,6,8 or in arteries other than of the CFA.…”
Section: Discussionmentioning
confidence: 99%